Transplantation of Hematopoietic Stem Cells Promotes Functional Improvement Associated with NT-3-MEK-1 Activation in Spinal Cord-Transected Rats - Xiong, Liu-Lin; Liu, Fei; Deng, Shi-Kang; Liu, Jia; Dan, Qi-Qin; Zhang, Piao; Zou, Yu; Xia, Qing-Jie; Wang, Ting-Hua (Frontiers in Cellular Neuroscience, 2017)
To investigate the effects of hematopoietic stem cells (HSCs) on the recovery of structure and function in the spinal cord transected (SCT) rats and explore associated mechanisms, 57 adult Sprague–Dawley rats were randomly divided into sham (n=15), SCT (n=24), and HSC transplantation groups (n=15). HSCs (passage 3) labeled by Hoechst 33342, were then transplanted intraspinally into the rostral, scar and caudal sites of the transected lesion at 14 days post operation. Both in vitro and vivo, HSCs exhibited the capacity of proliferation and differentiation. Following HSCs transplantation, BBB scores picked up significantly from week 4 to 24 after SCT, which was corresponding to the increased number of 5-HT fibers and oligodendrocytes , while the number of astrogliosis was decreased markedly indicated by immunohistochemical staining. Moreover, the decreased expression of neurotrophin 3 (NT3) and MEK-1 after SCT was effectively restored by HSCs transplantation. Together, the current study revealed that intraspinally administered HSCs in the chronic phase of SCT benefits the improvement of neurological function and the underlying mechanisms involved in the enhancement of 5-HT positive fibers and oligogenesis, and suppression of excessive astrogliosis, together with the upregulation of NT3-regulated MEK-1 activation in spinal cord. These crucial findings revealed not only the mechanism of cell therapy, but also may contribute to a novel therapeutic target for the treatment of SCI.